2011
DOI: 10.1186/1471-2164-12-133
|View full text |Cite
|
Sign up to set email alerts
|

A proteomics approach to decipher the molecular nature of planarian stem cells

Abstract: BackgroundIn recent years, planaria have emerged as an important model system for research into stem cells and regeneration. Attention is focused on their unique stem cells, the neoblasts, which can differentiate into any cell type present in the adult organism. Sequencing of the Schmidtea mediterranea genome and some expressed sequence tag projects have generated extensive data on the genetic profile of these cells. However, little information is available on their protein dynamics.ResultsWe developed a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 70 publications
3
29
0
Order By: Relevance
“…A proteomics approach to decipher the molecular nature of planarian stem cells recently identified a member of the hsp40/DnaJ gene family as a stem cell-specific hsp gene (Fernández-Taboada et al, 2011). The complete hsp40 planarian gene, identified in silico in S. mediterranea (genomic region v31.000.171), encodes a protein of 345 aminoacids, typified by the conserved J domain at the N terminus followed by a Gly/Phe-rich region ( Supplementary Fig.…”
Section: Hsp40/dnaj Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…A proteomics approach to decipher the molecular nature of planarian stem cells recently identified a member of the hsp40/DnaJ gene family as a stem cell-specific hsp gene (Fernández-Taboada et al, 2011). The complete hsp40 planarian gene, identified in silico in S. mediterranea (genomic region v31.000.171), encodes a protein of 345 aminoacids, typified by the conserved J domain at the N terminus followed by a Gly/Phe-rich region ( Supplementary Fig.…”
Section: Hsp40/dnaj Genesmentioning
confidence: 99%
“…Due to the presence of neoblasts, planarians may significantly contribute to the understanding of the role of HSPs in stem cells. While some studies have mainly focused on the role of HSPs as biomarkers of genotoxic stress in planarians (Guecheva et al, 2003;Sánchez Navarro et al, 2009), only recently hsp gene expression and function has been characterized in these organisms with the aim to assess how these proteins contribute to the mechanisms that regulate stem cell activity (Conte et al, 2009(Conte et al, , 2010Fernández-Taboada et al, 2011). Table I summarizes the current information on hsp genes recently characterized in planarians.…”
Section: Introductionmentioning
confidence: 99%
“…As Huang et al [41] suggested, small changes in gene expression can entail large effects on embryo development, and molecular differences between both types of embryos could be found at different levels from mRNA transcript abundance. Although cDNA analysis could improve mRNA EXPRESSION IN RABBIT EMBRYOS AFTER FREEZING our understanding of many processes, data generated are insufficient to explain complex cellular systems and often fail to reflect the influence of epigenetic changes, micro-RNA silencing, posttranscriptional modifications, or protein interactions [41,42]. Further analysis could find out which of the 70 transcript alterations observed goes one step beyond and has direct consequences on embryo physiology due to a change at the protein level.…”
Section: Discussionmentioning
confidence: 93%
“…Prominent among them were the homologues of the genes piwi, vasa, nanos, pumilio, tudor, bruno, MCM2, pcna, cyclin B, cbc, innexin, and many other found in microarrays studies and transcriptome and proteomic analyses (for further details see Reddien et al, 2005;Rossi et al, 2007;Oviedo and Levin, 2007;Eisenhoffer et al, 2008;Fernández-Taboada et al, 2011). These markers were used in the first single-cell simultaneous analysis of gene expression and cell cycle state of neoblasts using FACS and real-time PCR (Hayashi et al, 2010).…”
Section: Last Developments and The End Of The Storymentioning
confidence: 99%